graphically 3 x + y =1 and 2 y = 2 - 6 x
Answers
Answered by
1
Answer:
I gave second one answer or you in picture and I will give first answering in explanation.
Explanation:
(1)3x+ y-11=0,x- y-1=0, now 3 x+ y -11=0,y=11-3x when x = 0 we have y=11-3×0=11 when x equal to 3 we have y=11-3×3=2, thus we have following table here for x equal to 0 and 3 and for y= -1,2
Attachments:
![](https://hi-static.z-dn.net/files/d38/86d38227a08e8897419194d302c241cf.jpg)
![](https://hi-static.z-dn.net/files/d95/2399565a8ee5b5d47df869c4f2412ea1.jpg)
![](https://hi-static.z-dn.net/files/d68/1a76835b0b066883379aeceedb12205c.jpg)
![](https://hi-static.z-dn.net/files/de9/8ccead0c1876197e35455ed183f761b4.jpg)
![](https://hi-static.z-dn.net/files/dfe/685f2244259d2e0902fa794f11769bf1.jpg)
Similar questions